2019
DOI: 10.18805/ijar.b-3602
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for antimicrobial resistance in Escherichia coli isolates from poultry in Haryana

Abstract: Colibacillosis is a disease of severe economic significance to all poultry producers worldwide, characterized by a diverse array of lesions. Due to enormous exploitation of antibiotics in broilers, an increased number of resistant bacterial strains have developed in recent years. 106 E. coli strains were collected from broilers suffering from colibacillosis. The resistance to different classes of antimicrobials was determined. The presence of integrons was determined by Polymerase Chain Reaction (PCR). All the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…In the current study sixty-eight (61.8%) isolates were confirmed to be EHEC positive, which revealed five serotypes O157:H7 (12.7%), O26:H11 (21.8%), O128:H (10%), O111:H4 (9%) and O103:H2 (9%), while (30.9%) of isolates were EPEC with high prevalence of O127:H6 (17.2%). The obtained results are in parallel with those obtained by Kumar et al, (2003) who recorded that that the most common E. coli serogroups were O78 (23.5%) and Jin et al, (2008) who found that the most popular serotype of E. coli in avian diseases was O78 and O26. In addition, Hussein et al, (2022) recorded O127 in 15.7% of examined APEC from broiler affected with colibacillosis.…”
Section: -Discussionsupporting
confidence: 87%
“…In the current study sixty-eight (61.8%) isolates were confirmed to be EHEC positive, which revealed five serotypes O157:H7 (12.7%), O26:H11 (21.8%), O128:H (10%), O111:H4 (9%) and O103:H2 (9%), while (30.9%) of isolates were EPEC with high prevalence of O127:H6 (17.2%). The obtained results are in parallel with those obtained by Kumar et al, (2003) who recorded that that the most common E. coli serogroups were O78 (23.5%) and Jin et al, (2008) who found that the most popular serotype of E. coli in avian diseases was O78 and O26. In addition, Hussein et al, (2022) recorded O127 in 15.7% of examined APEC from broiler affected with colibacillosis.…”
Section: -Discussionsupporting
confidence: 87%
“…High sensitivity (100 per cent) of E. Coli isolates to CPZ has also been reported previously from Rajasthan, India (Dadheech et al, 2014) and from Czech Republic (94 per cent) (Kolář et al, 2002). On the contrary, a resistance of 56.6 per cent has been reported in poultry E. coli from Haryana (Kumar and Gupta, 2019). Similar to CPZ, high sensitivity to CX (100 per cent) has been reported from Rajasthan, India (Dadheech et al, 2014); from Australia (99.5 per cent) (Abraham et al, 2019); from Czech Republic (94per cent) (Kolář et al, 2002); from Tanzania (93.51 per cent) (Hamisi et al, 2014).…”
Section: Resultssupporting
confidence: 66%
“…Similar to CPZ, high sensitivity of E. coli isolates (100 per cent) to PIT has been reported from Czech Republic (Kolář et al, 2002) coli (100 per cent) has been reported from Ethopia (Sarba et al, 2019); Bangladesh (86 per cent) (Kmetova, 2009); from Bhubaneswar (83.04 per cent) (Senapati et al, 2020); Bangalore, India (75.39 per cent) (Sharada et al, 2009); from Egypt (63.1 per cent) (Younis et al, 2017). On the other hand high resistance of E. coli isolates to NX has been reported from Haryana, India (78.3 per cent) (Kumar and Gupta, 2019); and Anand, India (83.33 per cent) (Choudhari et al, 2020). With regards to NA, 83 per cent , 76.79 per cent isolates were reported sensitive from Egypt (Sarba et al, 2019) and Bhubaneswar (Senapati et al, 2020) whereas 81.2 per cent, 85.3 per cent, 100 percent isolates were reported resistant from China (Yassin et al, 2017), Jamaica (Miles et al, 2006) and Nigeria (Awogbemi et al, 2018), respectivley.…”
Section: Resultsmentioning
confidence: 99%
“…Young aged broilers exhibit high affinity to disease in compared to older chickens (Radwan et al, 2020) [18] . 106 E. coli isolates were also found by Kumar and Gupta (2019) [13] from broilers that had Coli bacillosis. All isolates were serotyped from National Salmonella and Escherichia Centre, Central Research Institute, Kasauli, (H.P.).…”
Section: Resultsmentioning
confidence: 63%